Penerapan Protokol Kesehatan Pada Mahasiswa Stikes Siti Hajar - Sulaiman Sulaiman; Anggriani Anggriani; Yeni Vera; Maryaningsih Maryaningsih (Jurnal Kesehatan dan Fisioterapi, 2021)
New normal is a phase where changes in human behavior will occur during the Covid-19  pandemic, where humans will limit all forms of physical touch and tend to limit touch with other individuals. The spread of Covid-19 can also happen to students if the implementation of the health protocol does not go well. Method. This research is a descriptive study with a cross-sectional approach. The population in this study were active students in the Stikes Siti Hajar Physiotherapy Program as many as 154 students. The sampling technique in this study used the accidental sampling technique. Results. Implementation of health protocols on the spread of Covid-19, with p < 0.010, level of knowledge p < 0.045, smaller than p < 0.05. Conclusion. There is a very significant influence on the application of health protocols and knowledge of the risk of being exposed to covid-19.Keywords: health protocol; covid-19 Ris; new normal